Analysis of the Effect of Recruitment, Management Efforts, Selection Criteria and Service Quality on Organizational Productivity with Employee Improvement as a Moderation Variable - Surya Bakti; Hwihanus (KALIANDA HALOK GAGAS, 2023)
Organizational productivity is certainly inseparable from the influence of employee recruitment, how management efforts include various policies and practices implemented by managers in an effort to improve employee performance and productivity, selection criteria refer to attributes or characteristics used to select new employees in the recruitment process, then the quality of service with the support of employee improvement. The purpose of this study is to prove the influence of recruitment, management efforts, selection criteria and also the quality of servants on organizational productivity. The second objective is to determine the effect of employee improvement on organizational productivity. This research design uses a quantitative research approach with primary data sources. The population of this study was teachers and employees of SMP – SMA Yayasan Mutiara Ilmu Kisaran as many as 60 respondents. This research analysis technique uses path analysis with the help of SmartPLS software Decision making in this study uses a P-Value value with a significance value of 0.05 with assumptions if the P-Value < 0.05 is declared to have a significant effect on each research variable with a P-Value value of 0.5198558. The results of this study prove that the effect of recruitment has a positive and significant effect on organizational productivity, and does not have a positive and significant effect on employee improvement. Management's efforts have no effect on organizational productivity and on the contrary have a positive effect on employee improvement. Selection criteria have a positive and significant effect on organizational productivity and selection criteria do not affect employee improvement. Service quality has a positive and significant effect on organizational productivity and service quality also has a positive and significant effect on employee improvement.